Gaps in the evidence on improving social care outcomes: findings from a meta‐review of systematic reviews. (26th October 2015) - Dickson, Kelly; Sutcliffe, Katy; Rees, Rebecca; Thomas, James
Abstract: Adult social care continues to be a central policy concern in the UK. The Adult Social Care Outcomes Framework (ASCOF) is a range of measures nationally available to drive forward improvement on outcomes and quality in local councils. While there is an emphasis on improving transparency, quality and outcomes, drawing on research evidence to achieve these aims is often difficult because the evidence is not easily identifiable, is disparate or of variable quality. We conducted a meta‐review to analyse and summarise systematic review‐level evidence on the impact of interventions on the four outcomes set out in the ASCOF: quality of life, delaying and reducing the need for services, satisfaction with services and safeguarding of vulnerable adults. This paper focuses on the availability of review‐level evidence and the presence of significant gaps in this evidence base. A range of health and social care databases were searched, including MEDLINE, ASSIA and The Cochrane Library in January and February 2012. All systematic reviews evaluating the efficacy of social care interventions for improving ASCOF outcomes for older people, people with long‐term conditions, mental health problems or physical and/or learning disabilities were eligible. Two reviewers independently screened systematic reviews for quality and relevance and extracted data; 43 systematic reviews were included, the majority of which examined the impact of interventions on quality of life ( n  = 34) and delaying and reducing the need for support ( n  = 25). Limited systematic review‐level evidence was found regarding satisfaction with services and safeguarding. There were also significant gaps in relation to key social care interventions and population groups. Research priorities include addressing these gaps and the collation of data on interventions, outcomes and populations more closely related to social care. Overall, a more relevant, comprehensive and robust evidence base is required to support improvement of outcomes for recipients of adult social care.